"In the Place Where There is no Darkness": Sexuality, Ideology and Space in George Orwell's 1984. Issue 4 (2nd October 2018) - Çelikkol, Aşkın
Abstract: George Orwell's dystopian novel 1984 owes its popularity to its figurative reflection of society as prison and to its pertinent illustration of panoptic elements that are of relevance in the contemporary world. Occupying a central place in the novel, the theme of surveillance has been critically assessed by a number of critics as disciplinary and punitive and as assaultive on the right to privacy. Taking its cue from theoretical models of space, the present article offers an alternative reading of the totalitarian state's appropriation of surveillance and claims that besides intruding into the private domains of the two main characters, the surveillance mechanism sets out to produce the conditions and the sites in which privacy is experienced. Addressing the love affair between Winston and Julia via spatial analyses, the article aims to present a dynamic interpretation of the relations between the governor and the governed, the surveillant and the surveilled.